Power to the people: hacking the city with plug-in interfaces for community engagement. - Hespanhol, Luke; Tomitsch, Martin (Springer Open, 2019)
This chapter presents a discussion about the design and development of bespoke "city hacking" initiatives focused on community engagement. The authors draw from the literature in the field to propose a definition of plug-in interfaces as portable interactive technology deployed directly to public spaces on a temporary basis and addressing pre-existing architectural and social affordances. They then present a series of short-term cross-sectional field studies where they make use of two distinct plug-in interfaces to contrast different design scenarios against three core contextual constraints: (1) technology familiarity of the interfaces; (2) level of integration of the interfaces into the built environment; and (3) nature of pedestrian activity ordinarily unfolding in the urban precinct. In the end the authors discuss the observations from the studies and derive some initial findings regarding the utilization of plug-in interfaces as tools for city hacking with the purpose of developing community engagement campaigns with rapid deployment and quick turnaround.
Keywords: Stadtsoziologie; Digitalisierung; Informationstechnologie; Partizipation; Stadtgesellschaft; Stadtsystem; Stadtgestaltung; Fußgänger